Cost-effectiveness analysis of tislelizumab plus chemotherapy as first-line treatment for HER2-negative advanced gastric or gastro-oesophageal junction adenocarcinoma - Zou, Liangliang; Guo, Guilan; Huang, Yufan; Yuan, Cuihua (Frontiers in Pharmacology, 2025)
BackgroundThe RATIONALE-305 trial indicates that tislelizumab plus chemotherapy (TLE-CHM) offers clinical benefits over placebo plus chemotherapy (PLB-CHM) as a first-line treatment for patients with HER2-negative advanced gastric or gastro-oesophageal junction (G/GEJ) adenocarcinoma. Nonetheless, incorporating tislelizumab results in higher treatment costs, raising concerns about its cost-effectiveness relative to PLB-CHM. This study aimed to assess the cost-effectiveness of TLE-CHM as an initial treatment for HER2-negative advanced G/GEJ adenocarcinoma from the perspective of the Chinese healthcare system.MethodsA Markov partitioned survival model incorporating three health states was developed to evaluate the cost-effectiveness of TLE-CHM as a first-line treatment for advanced G/GEJ adenocarcinoma. Clinical data were sourced from the RATIONALE-305 trial, with drug costs calculated at the national tender price, and additional costs and utility values derived from published literature. The outcomes measured included total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Sensitivity analyses were conducted to validate the model’s robustness.ResultsTLE-CHM achieved 1.53 QALYs at a cost of $23,484.39, compared to 1.14 QALYs at $12,123.52 for PLB-CHM. The ICER for TLE-CHM versus PLB-CHM was $29,608.51 per QALY gained. Key parameters influencing the model results included PFS utility, the cost of tislelizumab, and disease progression utility. At a willingness-to-pay threshold of $19,067 per QALY, TLE-CHM had an 0.8% probability of being cost-effective compared to PLB-CHM.ConclusionFrom the perspective of the Chinese healthcare system, TLE-CHM is not a cost-effective first-line treatment for advanced G/GEJ adenocarcinoma compared to chemotherapy.